DEMOCRACY AND ISLAMIC STUDIES AT PESANTREN - Munawir Munawir (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
Democracy here is not democratization as governance system,but democracy as spirit confession to the plural reality, including in Islamicstudies. Truly, undeniable that indoctrination approach have to beused in Islamic studies because with this approach Islamic values whichhave been believed the truth can be inculcated, so that every Moslem canlive as according to this values. It doesn’t mean that democratic approachmodel which emphasize at the process and reasoning cannot be appliedin Islamic studies. Herewith, Islamic studies traditions will always criticalanalyzed, so that will protected from intellectual saturation process (intellectualsuicide). With democracy principle, pesantren as entrance ofIslamic education system shall be always open to apply the good democratizationideas, in leadership style, even more in Islamic studies.